PROGRAMA DE ATENÇÃO AO IDOSO: A EXPERIÊNCIA DE UM MODELO ASSISTENCIAL - Eickhoff, Heloisa M.; Berlezi, Evelise M.; Oliveira, Karla R. d.; Dallepiane, Loiva B.; Perlini, Nara M. O. G.; Mafalda, Aline; Bueno, Cristiane (Salão do Conhecimento, 2013)
Resumo